Efeitos do consumo de sacarose sobre parâmetros metabólicos, desenvolvimentais e antioxidantes em Drosophila melanogaster: papel das plantas Syzygium cumini e Bauhinia forficata - Ecker, Assis (2014)
The fruit fly, Drosophila melanogaster, has been considered a suitable model organism for investigation of developmental/metabolic dysfunctions and therapeutic strategies. In this work Drosophila melanogaster larvae were used to evaluate the role of the plants Syzygium cumini and Bauhinia forficata on the effects triggered by consumption of high-sucrose diets (HSD) as oxidative stress markers and phenotypic responses associated to insulin signaling. The experiments were performed with first instar larvae (L1), collected 24 hr after egg deposition. The larvae were fed on high-sucrose diets (15 and 30%) supplied or not with 5mg/mL of S. cumini and B. forficata aqueous extracts. Newly-eclosed flies from larvae (1-3 day-old) were used to assess biochemical parameters. During the larval stage, 15% HSD and 30% HSD intake delayed the time to pupation and reduced the number of white pupa. The flies hatched from larvae treated with 30% sucrose also had a significant decrease in body weight compared with the flies from control group. The consumption of both diets increased the hemolymph glucose+treahalose levels and hemolymph/whole body homogenate triglycerides in adult flies. H202 levels were also increased in the homogenate of flies hatched from larvae grown on both diets when compared to control; however only 30% sucrose diet induced loss of mitochondrial viability. The intake of this diet also caused a decrease in the activity of superoxide dismutase, glutathione S-transferase, acetylcholinesterase and δ-D-aminolevulinate dehydratase enzymes as well as an increase in catalase activity in adult flies. Supplementation with S. cumini and B. forficata extracts reversed most of metabolic and developmental disorders caused by high sucrose diets. However, S. cumini extract was more efficient than B forficata in reducing hyperglycemia promoted by ingestion of both high sucrose diets and antioxidant status changes caused by 30% HSD. Overall, the obtained results highlight D. melanogaster as an effective model organism to investigate conditions that alter metabolic homeostasis and mainly point out the plant S. cumini as promising agent for studies related with metabolic disorders linked to excessive sugar.